KEUTAMAAN HAKAMAIN ATAS ALASAN SYIQAQ DI PENGADILAN AGAMA SAMARINDA - Hidayat Rahman (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT                                        This study, entitled "The virtue Hakamain Top Reasons Syiqaq In Samarinda Religious Court". Core issues that were examined in this study are: first, how the settlement divorce on the grounds syiqaq in the Religious Samarinda Court? second, how the procedures for the appointment hakamain the divorce case on the grounds syiqaq in the Religious Samarinda Court? third, whether the application of procedural hakamain in the case of divorce on the grounds syiqaq in Samarinda Religious Courts are in accordance with the Act - Act No. 50 of 2009? Based on the core issues above, the purpose of this study are: first, to explain what it hakamain as well as the functions, duties and powers. Second, explain the meaning syiqaq and various reasons. Third, explain the implementation hakamain in their divorce case on the grounds syiqaq in the Religious Samarinda.This research is descriptive research analysis. The approach taken is normative juridical approach that includes the history of law and comparative law. The data collection techniques through the study of literature and through field research. Data analysis techniques performed by juridical qualitative, and the results are set forth in the form of descriptive narrative.Based on the analysis the researchers did in order to answer the issues raised in this study, it can be concluded: first, settling disputes syiqaq the same as a regular divorce trial, which is the case registration must differentiate on grounds syiqaq from the beginning. Second, that the procedures for the appointment hakamain within reason of divorce on the grounds syiqaq is through interlocutory decision made judges who examined the case, before dropping a decision in which it is an incidental action of the judges. Hakamain from each party - each plaintiff and defendant in which they were proposed by the parties themselves. Third, the application hakamain in divorce cases must be in accordance with the laws - laws that apply and it is also the basis for the decision of the judges to examine cases of divorce on grounds syiqaq.On the basis of these conclusions the researchers propose suggestions: first, the need for public understanding of the steps - steps that must be taken before it filed for divorce in the Religious, especially on approaches amicably between a husband - wife who was bickering, so the expected effectiveness hakamain as emphasized by Al - Qur'an can be realized in the community, so the socialization of hakamain role can be further improved. Second, In an effort to reduce the number of divorce which included high within the jurisdiction of the Religious Court Samarinda, should the need for action - real action from relevant State Government agencies such as the Office of Religious Affairs, the Agency for Preservation Development Advisory Marriage (BP4) and agencies - other institutions that tekait the relationship of marriage and pre-marriage preparation for people - people who are ready to get married either in relation to maturity physically, spiritually and financially. With the expectation of future divorce for any reason including syiqaq that motivated by factors - factors mentioned above can be minimized as much as possible. Third, as a measure of academic need also held training for students of the Faculty of Law and Faculty of Shariah regarding the ability to be a mediator in reconciling the parties were bickering including syiqaq case is given in the existing curriculum at the Faculty of Law and Faculty of Sharia is still dominant limited Theoretically, so it needs to be balanced with practice-based curriculum. Where a mediator is not just only in the household problems as described above, but also a mediator could about what the fuss problems between individuals, between organizations with the organization, between individuals and organizations even from country to country.